Detection and analysis of cortical beta bursts in developmental EEG data. (April 2022) - Rayson, Holly; Debnath, Ranjan; Alavizadeh, Sanaz; Fox, Nathan; Ferrari, Pier F.; Bonaiuto, James J.
Abstract: Developmental EEG research often involves analyzing signals within various frequency bands, based on the assumption that these signals represent oscillatory neural activity. However, growing evidence suggests that certain frequency bands are dominated by transient burst events in single trials rather than sustained oscillations. This is especially true for the beta band, with adult 'beta burst' timing a better predictor of motor behavior than slow changes in average beta amplitude. No developmental research thus far has looked at beta bursts, with techniques used to investigate frequency-specific activity structure rarely even applied to such data. Therefore, we aimed to: i) provide a tutorial for developmental EEG researchers on the application of methods for evaluating the rhythmic versus transient nature of frequency-specific activity; and ii) use these techniques to investigate the existence of sensorimotor beta bursts in infants. We found that beta activity in 12-month-olds did occur in bursts, however differences were also revealed in terms of duration, amplitude, and rate during grasping compared to adults. Application of the techniques illustrated here will be critical for clarifying the functional roles of frequency-specific activity across early development, including the role of beta activity in motor processing and its contribution to differing developmental motor trajectories. Highlights: Transient bursts rather than oscillations dominate sensorimotor beta activity Lagged coherence indicates the rhythmicity of a signal The p-episode method can be used to identify beta bursts in developmental EEG data Infant sensorimotor beta has a lower peak frequency than adults and consists of longer duration, higher amplitude bursts